Kinesiology of the musculoskeletal system - Neumann, Donald A. (Elsevier, 2017)
With a focus on the normal and abnormal mechanical interactions between the muscles and joints of the body, Neumann's Kinesiology of the Musculoskeletal System, 4th Edition provides a foundation for the practice of physical rehabilitation. This comprehensive, research-based core text explores kinesiology as it relates to physical rehabilitation in a clinically relevant and accessible manner. It presents the language of human movement - and acts as a bridge between basic science and clinical management. It helps clinicians effectively address the mechanical-based changes in movement across a person's lifespan, whether in the context of rehabilitation, recreation, or promotion of health and wellness. Full-color anatomic and kinesiologic illustrations clearly demonstrate the anatomy, functional movement, and biomechanical principles underlying movement and posture. An eBook version, included with print purchase, provides access to all the text, figures, and references, with the ability to search, customize content, make notes and highlights, and have content read aloud. The eBook included with print purchase also features multiple excellent videos of anatomic and kinesiologic principles, answers to study questions from the print book, and additional tables and figures. Evidence-based approach emphasizes the importance of research in PT decision-making. More than 900 high-quality illustrations provide visual accompaniments to clarify the material. Clinical Connections boxes at the end of each chapter highlight or expand upon a particular clinical concept associated with the kinesiology covered in the chapter. Special Focus boxes throughout the text provide numerous clinical examples to demonstrate why kinesiologic information is needed. Critical thinking questions for selected chapters reinforce the main concepts.